2018
DOI: 10.1111/ssqu.12477
|View full text |Cite
|
Sign up to set email alerts
|

Headwinds, Tailwinds, and Preferences for Income Redistribution

Abstract: Objective This study examines how preferences for income redistribution respond to information that points to the degree to which bad luck causes poverty and good luck causes wealth. Methods Survey respondents saw a vignette that described why someone is poor or a vignette that described why someone is wealthy; poverty and wealth were products of effort, various mixtures of effort and luck, one dimension of luck, or two dimensions of luck. Results Overall trends in the data show that redistribution is viewed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
1
7
1
Order By: Relevance
“…Some relatively recent experimental research offers evidence to suggest that exposure to inequality may shape their thinking about the issues in various ways (Chavanne 2018;Heiserman and Simpson 2017;McCall et al 2017;Sands 2017). McCall et al (2017), for example, found that introducing people to information about growing inequality made them more likely to attribute success and failure to structural explanations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some relatively recent experimental research offers evidence to suggest that exposure to inequality may shape their thinking about the issues in various ways (Chavanne 2018;Heiserman and Simpson 2017;McCall et al 2017;Sands 2017). McCall et al (2017), for example, found that introducing people to information about growing inequality made them more likely to attribute success and failure to structural explanations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, high levels of segregation by race and social class may skew how Americans perceive inequality, as they are often surrounded by those who share their outlooks and social position in life. Recent experimental work provides suggestive evidence that social context shapes individuals' perceptions about whether inequality should be reduced (Chavanne 2018; Heiserman and Simpson 2017;McCall et al 2017;Sands 2017). Other evidence suggests that higher inequality in US states associated with a reduced sense of financial satisfaction (Hastings 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, high levels of segregation by race and social class may skew how Americans perceive inequality, as they are often surrounded by those who share their outlooks and social position in life. Recent experimental work provides suggestive evidence that social context shapes individuals’ perceptions about whether inequality should be reduced (Chavanne 2018; Heiserman and Simpson 2017; McCall et al 2017; Sands 2017). Other evidence suggests that higher inequality in U.S. states is associated with a reduced sense of financial satisfaction (Hastings 2019).…”
mentioning
confidence: 99%
“…The study manipulates debtor and lender responsibility for two reasons. First, vignette-based studies have found that preferences for redistribution are stronger (weaker) when respondents perceive that one's situation is within (beyond) one's control (Schokkaert & Overlaet, 1989;Schokkaert & Capeau, 1991;Konow, 1996Konow, , 2001Konow, , 2003Konow, , 2009Faravelli, 2007;Chavanne, 2016Chavanne, , 2018. Additionally, large-scale national or international surveys show a robust relationship between preferences for redistributive policies and perceptions that life situations are products of effort or luck (Fong, 2001;Alesina & La Ferrara, 2005;Boarini & Le Clainche, 2009).…”
mentioning
confidence: 99%
“…Although the present study and the study described by Chavanne (2017) are the first attempts to analyze public perceptions of debt relief using vignettes, the method used in these studies is commonly used in social science research to examine how judgments respond to changes in social context. In addition to the work cited above involving vignette-based studies of the effect of responsibility on redistributive preferences (Schokkaert & Overlaet, 1989;Schokkaert & Capeau, 1991;Konow, 1996Konow, , 2001Konow, , 2003Konow, , 2009Faravelli, 2007;Gaertner & Schokkaert, 2012;Chavanne, 2016Chavanne, , 2018, vignettes have been used to study topics that include, but are not limited to, how fairness judgments respond to price and wage increases (Kahneman et al, 1986), to alternative resource distributions (Yaari & Bar-Hillel, 1984), to changes in causation and culpability (Alicke, 1992;Hitchcock & Knobe, 2009;Alicke et al, 2011), to changes in criminal sentencing severity (Robinson & Darley, 1995;Carlsmith et al, 2002;Robinson & Kurzban, 2006) and to different degrees of deception (Gneezy, 2005).…”
mentioning
confidence: 99%